Ultrashort-Pulse Laser Systems Based on External-Cavity Mode-Locked InGaAs-GaAs Semiconductor Oscillators and Semiconductor or Yb:Fibre Amplifiers - Budz, Andrew John (My University, 2008)
This thesis describes the development of a tunable, ultrashort-pulse semiconductor-based laser system operating in the 1 μm wavelength region. The design of the oscillator is based on a two-contact long-wavelength InGaAs-GaAs quantum-well semiconductor device containing integrated gain and saturable absorber sections. A key design component of the oscillator is the fabrication of a curved ridge-waveguide in the gain section of the device, which allows the laser to be operated in a compact, linear external cavity. Under conditions of passive or hybrid mode-locking, the semiconductor oscillator can generate pulses of 1 to 10 ps in duration, which are tunable from 1030 to 1090 nm. The oscillator is also capable of being passively mode-locked at harmonics of the cavity round-trip frequency, allowing tuning of the pulse repetition rate from 0.5 to over 5 GHz. Noise measurements on two independently hybridly mode-locked semiconductor lasers reveal that the absolute noise of each laser is dominated by phase noise at frequencies below 10^5 Hz, while amplitude noise dominates at higher frequencies.
Semiconductor and fibre optical amplifiers are used to scale the average power level of the mode-locked pulses. Semiconductor optical amplifiers consisting of narrow-stripe and flared-waveguide designs have been fabricated using the same material structure as that of the mode-locked semiconductor oscillator. Narrow-stripe devices with a length of 800 μm have produced amplified average signal powers of 13 mW, while 1700-μm-long, 2° flared-waveguide devices have produced amplified average signal powers of 50 mW. A fibre-based system consisting of a single-mode double-clad Yb-doped fibre has been constructed to investigate the suitability of a mode-locked diode laser as a seed-source for a Yb:fibre amplifier. Amplified average signal powers of up to 1.4 W have been obtained at the output of the fibre for a launched pump power of 2.1 W. Compression of the amplified pulses using a modified dual-grating compressor yields pulse durations as low as 500 fs and a peak power of up to 1.5 kW.
Preliminary work is reported on the development of a novel dual-wavelength optical source consisting of two synchronized mode-locked diode lasers and a polarization-maintaining Yb:fibre amplifier. Numerical simulations based on a rate-equation model for the amplifier gain are conducted to investigate the performance characteristics of a Yb:fibre amplifier when operated under dual-wavelength signal amplification. The simulations are used to predict and optimize the performance of the fibre amplifier for two mode-locked semiconductor-seed-oscillators operating at wavelengths of 1040 and 1079 nm. Good agreement is obtained between the simulations and experimental results.
Pages 10, 46, 126, 142 and 146 have been omitted because they were completely blank.
Keywords: ultrashort-pulse, semiconductor, laser, system, InGaAs-GaAs, oscillator